2019
DOI: 10.1155/2019/1625678
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Cryptosystem for Video Surveillance in the Internet of Things Environment

Abstract: Surveillance systems paradigm envisions the pervasive interconnection and cooperation of interactive devices over the Internet infrastructure. Nevertheless, dissemination and processing of surveillance video amid the Internet of Things (IoT) applications become a susceptible issue due to the large volume and the significant information of these data. Moreover, surveillance devices on IoT have very limited resources such as memory and storage. The actual security methods are not quite appropriate for surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Observational findings confirmed the suggested cryptosystem's efficiency with respect to reliability and highlevel protection relative to many other modern image cryptographic algorithms. During most of the distribution of essential keyframes to customized WCE healthcare providers and gastroenterologists, Hamza et al [42] reported an effective cryptosystem for IoT-based monitoring systems.…”
Section: Preliminary Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational findings confirmed the suggested cryptosystem's efficiency with respect to reliability and highlevel protection relative to many other modern image cryptographic algorithms. During most of the distribution of essential keyframes to customized WCE healthcare providers and gastroenterologists, Hamza et al [42] reported an effective cryptosystem for IoT-based monitoring systems.…”
Section: Preliminary Workmentioning
confidence: 99%
“…e outcomes of the proposed methodology are fairly reasonable as well as nearly ideal standards. We compared proposed methods with past referenced schemes such as [20,39,41,42,50,71]. We noticed that the referenced surveillance and encryption scheme is produced relative results to attain confidentiality of the security.…”
Section: Comparative Analysis Among the Monitoring And Surveillance S...mentioning
confidence: 99%
“…To increase distributed video surveillance systems' resiliency and intelligence, network bandwidth and reaction time between wireless cameras and cloud servers are being reduced in the Internet-of-things (IoT). In [9], an effective cryptosystem is used to create a safe IoT-based surveillance system. ere are three parts to it.…”
Section: Related Workmentioning
confidence: 99%
“…Hamza et al [23] addressed a new idea which is efficient cryptosystem to provide security into secure surveillance approach at the IoT ecosystem. Further explanation of the cryptosystem, he mentioned that this approach has three-fold.…”
Section: Related Workmentioning
confidence: 99%
“…In which our proposed method has gaining impetus in each mentioned area. We compared with other methods such as [11], [31], [23] and [24]. Each method has proposed good values and tried to cover confidentiality of the secure parameter of the image encryption.…”
Section: F Comparative Anlysis With Existing Surveilance Schemesmentioning
confidence: 99%